Development and validation of an high-performance liquid chromatographic, and a ultraviolet spectrophotometric method for determination of Ambroxol hydrochloride in pharmaceutical preparations - Selvadurai Muralidharan; Jaya Raja Kumar; Sokkalingam Arumugam Dhanara (Wolters Kluwer Medknow Publications, 2013)
A high-performance liquid chromatographic (HPLC) and ultraviolet (UV) methods were developed and validated for the quantitative determination of Ambroxol hydrochloride (AMH) in pharmaceutical dosage form. HPLC was carried out by reversed phase (RP) technique on an RP-18 column with a mobile phase composed of acetonitrile and water (pH 3.5 adjusted with orthophosphoric acid [60:40, v/v]). UV method was performed with the λmax at 250 nm. Both the methods showed good linearity, reproducibility, and precision. No spectral or chromatographic interferences from the tablet excipients were found in UV and HPLC. The method was successfully applied to commercial tablets. Validation parameters such as linearity, precision, accuracy, and specificity were determined. The HPLC Limit of detection (LOD) and Limit of quantification (LOQ) for Ambroxol were found to be 1 and 5 ng/ml, respectively. The UV LOD and LOQ for Ambroxol were found to be 1 and 4 μg/ml, respectively. The results were statistically compared using one-way analysis of variance. The proposed economical method could be applicable for routine analysis of AMH and monitoring of the quality of marketed drugs.